2020
DOI: 10.3390/cancers12092605
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms Accounting for the Refractoriness of Colorectal Carcinoma to Pharmacological Treatment

Abstract: The unsatisfactory response of colorectal cancer (CRC) to pharmacological treatment contributes to the substantial global health burden caused by this disease. Over the last few decades, CRC has become the cause of more than 800,000 deaths per year. The reason is a combination of two factors: (i) the late cancer detection, which is being partially solved by the implementation of mass screening of adults over age 50, permitting earlier diagnosis and treatment; (ii) the inadequate response of advanced unresectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 238 publications
(267 reference statements)
0
21
0
Order By: Relevance
“…As illustrated in Figure 1B, the collision of the DNA replication fork, together with this ternary complex formation, ultimately results in lethal and irreversible double-strand breaks [4] . Individual differences in metabolic capacities should thus be considered for individualized irinotecan therapy [5] . The mechanism of the anti-cancer activity of SN-38 is the stabilization of the DNA Top1-DNA cleavable complex in cancer cells, resulting in the arrest of DNA replication [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Figure 1B, the collision of the DNA replication fork, together with this ternary complex formation, ultimately results in lethal and irreversible double-strand breaks [4] . Individual differences in metabolic capacities should thus be considered for individualized irinotecan therapy [5] . The mechanism of the anti-cancer activity of SN-38 is the stabilization of the DNA Top1-DNA cleavable complex in cancer cells, resulting in the arrest of DNA replication [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Even though various human cancers are treated with irinotecan, refractoriness remains a significant problem, as is the case with most other anti-cancer drugs. With regard to drug therapy for colorectal cancer (CRC), cellular and molecular mechanisms of failure in irinotecan therapy seem to be roughly classified into the following six categories: (1) drug uptake and export; (2) drug metabolism; (3) changes in drug targets; (4) phenotype transition; (5) adaptation to the tumor microenvironment; and (6) colon cancer stem cells (CSCs) [6] .…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to identify mechanisms of resistance to FOLFOX, the most frequently prescribed regimen in patients with stage II and IV CRC 13 . While various mechanisms have been identified for oxaliplatin or 5-FU monotherapy (including proteins involved in drug uptake, export and metabolism, modulation of thymidylate synthase expression, or alterations of apoptosis/survival effectors, as reviewed), there are few preclinical studies investigating resistance to 5-FU/Oxaliplatin combinations 37 . Among those, previous studies have suggested that ERCC1 over-expression, leading to increased DNA damage repair through the nucleotide excision repair pathway, correlates with FOLFOX resistance 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the miR-34a mimic MRX34 is the first synthetic miRNA entered into clinical trials (for an extensive review on the topic, see [36]). Other mechanisms of resistance to 5-FU, and chemotherapy in general, have been reported, such as altered expression of drug uptake carriers and efflux pumps, changes in phase I and phase II enzymes involved in drug metabolism (resulting in decreased pharmacological action either by an enhanced generation of inactive metabolites or diminished activation of prodrugs), altered expression levels of drug targets (such as thymidylate synthase, the target of 5-FU), enhanced capacity of tumor cells to repair the DNA damage usually induced by chemotherapeutic drugs or, to the contrary, dysfunction of the DNA damage sensing machinery and inability to undergo cell death after exposure to DNA damaging chemotherapy (such as upon TP53 loss) (for an extensive review on the topic, see [40]).…”
Section: Therapy and Drug Resistancementioning
confidence: 99%